Feminização do jornalismo e desigualdades de gênero no exercício da profissão em Goiânia - Morais, Ana Maria de (2018)
This research investigates the implications of the feminization of journalism and gender inequalities in the practice of journalism from the perspective of 20 women who worked or works in the profession in Goiânia. Through their experiences, the conditions of work, the changes brought about by the new communication technologies and the precariousness of the profession are analyzed. It also investigates the relations of the journalists with the head, with the colleagues, with the direction of the company and with the sources, as well as the experiences of those who have performed or are in the position of leadership. The interviewees report cases of moral and sexual harassment, situations of sexism, male chauvinism and other discrimination based on gender differences, which also intersect with other elements, such as race, class and origin. The professionals reveal their conceptions of gender and reflect on the ideologies that are passed on by journalism as a producer of meanings and legitimator of values and visions circulating in the social environment. In addition, the reconciliation between work and personal life is analyzed, since the exercise of journalism requires dedication and reproductive work remains a feminine responsibility. In the effort to perceive transformations and continuities, the interviewees are journalists who began to work in the profession in the 1970s, 1980s, 1990s, 2000s and 2010. The theoretical-methodological basis is developed from studies on journalism, which talk about the ways of producing news and the identity of the journalist; and gender studies that raise questions about the naturalized behaviors of sexism practiced by both men and women that result in different types of oppression, backed by biological differences and the presumption of male superiority.